New Approach for Characterization and Mitigation of the Swelling Phenomenon - Bouassida, Mounir; Manigniavy, Sergio Andrew; Azaiez, Dalel; Bouassida, Yosra (Frontiers in Built Environment, 2022)
This article first introduces a new method of characterization of expansive clays after oedometer test results performed on intact saturated clay specimens. On the presumed expansive clays specimens, oedometer tests are preceded by the free swelling test from which the swelling pressure is measured. From current oedometer test results carried out on expansive and non-expansive clays, the ratio of compression index (Cc) by the swelling index (Cs) was determined. A threshold value of the ratio Cc/Cs was identified to distinguish between expansive clay specimens and non-expansive clay specimens. Second, a novel mitigation method of the swelling phenomena was validated by performing oedometer tests on expansive clay specimens preceding the measurement of swelling pressure. Oedometer tests performed on a 53% thickness clay specimen overlaid by a 47% thickness of sand showed a significant reduction of the swelling pressure compared to that measured on a full expansive clay specimen. The mitigation solution reduced the swelling effect by placing a compacted granular layer as an interface between the expansive clay and the foundation. This solution has been adopted and approved in forthcoming a lightweight building construction at the Faculty of Sciences of Tunis City.